Cultural Heritage as Potential for Tourism in the Lower Danube Basin in Serbia - Basarić, Jelena (Arhitektura i urbanizam, 2023)
The Lower Danube Basin boasts rich and quite diverse cultural heritage, which can be pivotal for the development of tourism and an important factor with regard to social and economic changes in Eastern Serbia. As a result of cultural heritage, numerous European and world capitals have invested effort in developing destinations and sites that promote cultural content and attractions. Cultural values and traits from different historical periods attract more and more tourists, thus increasing interest in cultural tourism. Cultural heritage adds value to the basic tourist content, greatly contributing to increased tourist traffic and the promotion of local communities, but also to the further development and improvement of tourist offers. When it comes to cultural tourism in the Lower Danube Basin, it must be stressed that there is no individual or common tourism development strategy in this area. This paper is aimed at presenting historical heritage as cultural potential for tourist valorisation, impacting the local, regional and national environment. Cultural heritage can play a decisive role in creating a cultural and tourist development policy in the area of the Lower Danube Basin, having in mind the method of managing cultural values and possibilities in order to harmonise them with other kinds of tourism. The purpose of this paper is to highlight the potential of cultural heritage, which would contribute to shaping the cultural and tourist identity of this area in both local and international tourist markets.
Keywords: tourist potential; cultural heritage; protection; improvement; Lower Danube Basin